The Choreography: Chula Moulee - Phetruchee, Mananshaya (Journal of Cultural Approach, 2024)
The research article examined the Chula Moulee, a synthetic dance, aim to create a performance through creative research. The article incorporates concepts and theories of artificial dance with practices to analyze the data, which is then used to create a performance. According to the research, the Chula Moulee dance consists of seven elements: concept, actors, lyrics and music, choreography, costumes, space, and props. If we appreciate the Chula Moulee performance beyond its artistic beauty, we can recognize the meaning and great deeds of Prince Siddhartha and learn Dhamma through another medium. This implementation is valuable for education and performances. Experts found significances of the Chula Moulee’s performance at a score of 84 percent.